2016
DOI: 10.1016/j.cortex.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Differential compromise of prospective and retrospective metamemory monitoring and their dissociable structural brain correlates

Abstract: Metamemory refers to personal knowledge about one’s own memory ability that invokes cognitive processes relevant to monitoring and controlling memory. An impaired monitoring system can potentially result in unawareness of symptoms as can occur in addiction denial. Monitoring processes can be assessed with prospective measures such as Feeling-Of-Knowing (FOK) judgments on prediction of future recognition performance, or retrospective confidence judgments (RCJ) made on previous memory performance. Alcoholic pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
48
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(54 citation statements)
references
References 56 publications
5
48
1
Order By: Relevance
“…Using an episodic FOK paradigm, a recent paper reported that structural integrity of the right insula supported memory awareness in a mixed group, which included patients with mild Alzheimer's disease and cognitively healthy older adults (Cosentino et al, 2015). Similarly, we found that FOK accuracy was selectively related to volumes of the insula in the uncomplicated alcoholics involved in the present study (Le Berre et al, 2016). Because the insula has been identified as a critical neural substrate of multiple components of self-awareness (Craig, 2009; Schmitz & Johnson, 2007), we posited that prospective episodic FOK implicates online memory monitoring mechanisms and additional self-referential processes to generate accurate future estimations.…”
Section: Introductionsupporting
confidence: 78%
See 4 more Smart Citations
“…Using an episodic FOK paradigm, a recent paper reported that structural integrity of the right insula supported memory awareness in a mixed group, which included patients with mild Alzheimer's disease and cognitively healthy older adults (Cosentino et al, 2015). Similarly, we found that FOK accuracy was selectively related to volumes of the insula in the uncomplicated alcoholics involved in the present study (Le Berre et al, 2016). Because the insula has been identified as a critical neural substrate of multiple components of self-awareness (Craig, 2009; Schmitz & Johnson, 2007), we posited that prospective episodic FOK implicates online memory monitoring mechanisms and additional self-referential processes to generate accurate future estimations.…”
Section: Introductionsupporting
confidence: 78%
“…Further, we explored whether these brain activation and functional connectivity patterns during predictions of future recognition performance could contribute to subsequent memory performance, especially because efficient metamemory skills are implicated in efficient use of memory skills in daily life activities. Previously, we demonstrated that the insula was a key selective structural brain substrate of FOK accuracy in sober alcoholics participating in the present study (Le Berre et al, 2016). Herein, we used functional imaging to test the hypothesis that attenuated activation of the insula and compromised insula functional connectivity would contribute to overestimation of memory performance by uncomplicated alcoholics.…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations